Flexural behaviour of reinforced concrete beam with rectangular web opening - Nur Iffah Izzati, Aziz (2017)
Beam is the structural element which is able to withstand the load primarily by resisting against bending. Provision of utility and service ducts are important part of modern building construction. To facilitate fast and uninterrupted progress, the layouts of these ducts are planned in advance. Opening in a beam is a facility that is necessary to accommodate services such as electricity, sewage, water supply, computer network, telephone, and air-conditioning. This study focused on the flexural behavior of reinforced concrete beam with different size of rectangular opening. The study indicated that beam with small rectangular opening has smaller flexural strength compared with control beam. This study also shows beam with large opening possessed the lowest flexural strength among the samples. It can be concluded that the increase in the depth size of rectangular opening will cause the reduction of ultimate strength in beam.